Optimization of gembili (Dioscorea esculenta L.) starch partial hydrolysis in maltodextrin production with microwave assist using acetic acid catalyst - Shalihin, Muhammad Zaki Riadhus; Paramita, Vita; Sitio, Septi Enjelina; Nurlaili, Fitri Dwi; Ariyanto, Hermawan Dwi (Jurnal Rekayasa Proses, 2024)
The purpose of this study was to determine the optimal conditions for partial hydrolysis of gembili starch in the maltodextrin production. Novelty of this research is the use of acetic acid as a substitute for commonly used acids and microwaves for process efficiency. The process of maltodextrin production includes raw material pretreatment, gelatinization, liquefaction, drying and analysis. Variations in liquefaction time (30, 40, 50 min), microwave power (300, 400, 500 W) and acetic acid concentration (14, 15, 16 %) were used as independent variables. The equivalent dextrose analysis results were 9.389 ± 0.042 to18.980 ± 0.201%, the density analysis results were 1.059416 to 1.107796 g/ml and viscosity analysis results were 0.430554 to 0.974663 cP. This study produces that 96.705% of the total variability in response can be explained in the regression equation. Critical value of this study estimated dextrose equivalent value of maltodextrin produced of 16.636% and the validation of it is 16.254 ± 0,074%.